PEMBUATAN EDIBLE FILM BERBAHAN GELATIN KULIT SAPI SPLIT DENGAN PENAMBAHAN LEVEL GLISEROL - Dwi Wulandari (Politeknik ATK Yogyakarta, 2016)
Gelatin is one type of protein extracted from skin collagen tissue, bone or animal ligament. One potential raw material is bovine split leather which is a byproduct of the tanning industry. One of the properties of gelatin that is shape of forming a film commonly known as edible films.The aims of this study was to know the properties of edible film of gelatin bovine leahther split with the addition of different levels of glycerol. RAL pattern studies using a factorial 2 x 3 with 2 levels of gelatin (4 g and 6 g) and 3 levels of glycerol (30%, 40%, 50%), with three replication. When there are real differences continued with Duncan's test mutiple Range Test (DMRT). The results edible film shows the average water content of 15.18%; thickness 0.15 mm; solubility of 9.9%; tensile strength of 0.94 MPa; 68.26% elongation and WVTR 22.28 g. H2O.m2.h-1. The result edible films can be used to wrapping that do not require high tensile strength, elongation and solubility. Keywords : bovine leather split, gelatin, edible film, glycerol